2016
DOI: 10.1007/s10763-016-9781-3
|View full text |Cite
|
Sign up to set email alerts
|

Transposition of Knowledge: Encountering Proportionality in an Algebra Task

Abstract: This article reports on an analysis of the process in which knowledge to be taught was transposed into knowledge actually taught, concerning a task including proportional relationships in an algebra setting in a grade 6 classroom. We identified affordances and constraints of the task by describing the mathematical praxeology of the two different types of knowledge exposed, in the task as such and in the activity of the classroom. Through the teacher's explicit process of reasoning, modeling, revising, solving,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
(32 reference statements)
2
16
0
1
Order By: Relevance
“…Ayan and Isiksal-Bostan (2018) also indicated that students make comparisons in the process of solving proportional reasoning problems related to geometric shapes, while giving arbitrary values to the lengths. Lundberg and Kilhamn (2018) emphasized that students are dealing with proportional reasoning problems through trial and error. In addition, Lundberg and Kilhamn (2018) determined that students also use the strategies like direct proportion and doubling or halving during the proportional reasoning process.…”
Section: Students' Cognitive Strategies In Solving Proportional Reasomentioning
confidence: 99%
See 1 more Smart Citation
“…Ayan and Isiksal-Bostan (2018) also indicated that students make comparisons in the process of solving proportional reasoning problems related to geometric shapes, while giving arbitrary values to the lengths. Lundberg and Kilhamn (2018) emphasized that students are dealing with proportional reasoning problems through trial and error. In addition, Lundberg and Kilhamn (2018) determined that students also use the strategies like direct proportion and doubling or halving during the proportional reasoning process.…”
Section: Students' Cognitive Strategies In Solving Proportional Reasomentioning
confidence: 99%
“…Lundberg and Kilhamn (2018) emphasized that students are dealing with proportional reasoning problems through trial and error. In addition, Lundberg and Kilhamn (2018) determined that students also use the strategies like direct proportion and doubling or halving during the proportional reasoning process. Langrall and Swafford (2000) stated that students use pictures, models or manipulatives to understand proportional reasoning problems and to make a qualitative comparison.…”
Section: Students' Cognitive Strategies In Solving Proportional Reasomentioning
confidence: 99%
“…In the present study, I have employed praxeology to analyse the didactic transposition of rational numbers. The study focuses only on knowledge to be taught and taught knowledge (Lundberg & Kilhamn, 2018;Pansell & Boistrup, 2018). The knowledge to be taught is investigated through analysing a mathematics textbook for teacher education.…”
Section: Theoretical Framework: Didactic Transpositionmentioning
confidence: 99%
“…Moreover, following ATD, our approach regarded textbooks as an empirical source which can reveal knowledge to be taught in the didactic transposition process; this differs from the approaches of previous textbook research studies. Although there are some existing studies using ATD for textbook analysis (González-Martîn, Giraldo, & Souto, 2013;Lundberg & Kilhamn, 2018;Wijayanti, 2015;Wijayanti & Winsløw, 2017), the innovation this paper provides is in the precision achieved at the logos level. The theoretical and methodological aspects of this study can contribute to future research on mathematics textbooks.…”
Section: Implications and Limitationsmentioning
confidence: 99%